A Robust and Rapid Candidate Gene Mapping Pipeline Based on M2 Populations - Zhou, Huangkai; Tang, Kuanqiang; Li, Guang; Liu, Wenqiang; Yu, Hui; Yuan, Xiaohui; Yang, Suxin; Bhattacharyya, Madan K.; Feng, Xianzhong (Frontiers in Plant Science, 2021)
The whole genome sequencing-based bulked segregant analysis (WGS-BSA) has facilitated mapping candidate causal variations for cloning target plant genes. Here we report an improved WGS-BSA method termed as M2-seq to expedite mapping candidate mutant loci by studying just M2 generation. It is an efficient mutant gene mapping tool, rapid and comparable to the previously reported approaches, such as Mutmap and Mutmap+ that require studying M3 or advanced selfed generations. In M2-seq, background variations among the M2 populations as compared to the reference genome sequence can be removed efficiently without knowledge of the variations of the mutant progenitor plant which without chemical mutagenesis. Furthermore, use of absolute delta single nucleotide polymorphism (SNP) index values can effectively remove the background variation caused by repulsion phase linkages of adjacent mutant alleles; and thereby, facilitates identification of causal mutation in target genes. Here we demonstrated the application of M2-seq in successfully mapping genomic regions harboring causal mutations for mutant phenotypes among 10 independent M2 populations of soybean. Mapping candidate mutant genes just in M2 generation with the aid of M2-seq method should be particularly useful in expediting gene cloning especially among the plant species with long generation time.